THE EFFECTIVENESS OF SELF-HELP APPLICATION BASED ON SELF DIRECTED SEARCH IMPROVES STUDENT CAREER EXPLORATION - Ade Yudha Prasetyo Hutomo; Budi Purwoko; Budiyanto Budiyanto (Jurnal Dedikasi Pendidikan, 2024)
This study aims to produce career field applications that meet acceptability criteria which include aspects of usability, feasibility, accuracy and compliance for guidance and counseling teachers at SMPN 1 Beji as a guide in providing guidance and counseling to class VIII students at SMPN 1 Beji. This development was carried out based on the distribution of a needs questionnaire in class VIII to guidance and counseling teachers in charge of class VIII and class VIII students totaling 372 students. This research uses the Borg & Gall development method. The development of this application is used by guidance and counseling teachers for additional information in career counseling and guidance activities. The development of the SDS Self Help application for class VIII students of SMPN 1 Beji was tested to see the acceptability and effectiveness of the application for class VIII students. Therefore, tests were carried out on material experts, media, prospective users (guidance and counseling teachers for class VIII) and class VIII students. The results of the test get a score of 0.9, it can be concluded that the product is very good, does not need to be revised. In testing the effectiveness of the application using the Wilcoxon Signed Rank Test which was conducted on 372 class VIII students, it was seen that the application was effectively used, so that the development of the SDS Self Help application for Class VIII SMPN 1 Beji met the acceptability criteria